Financial Performance Analysis of Islamic Commercial Banks in Indonesia Using the Sharia Conformity and Profitability (SCnP) Method during the 2019–2023 Period - Fransiska, Alda Tri; Nurdin, Ade Ali; Setiawan, Setiawan; Nuryati, Neneng (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
As Islamic banking develops in Indonesia, its sharia compliance needs to be measured. This study aims to determine the financial performance of Islamic commercial banks in Indonesia using the Sharia Conformity and Profitability (SCNP) model. The financial performance of Islamic commercial banks is measured using the ratios in the Sharia Conformity and Profitability (SCNP) model, including Islamic Investment, Islamic Income, Profit Sharing Ratio, Return on Assets (ROA), Return on Equity, and Net Profit Margin (NPM). The data collection technique used is the documentation technique, in this study the author uses the Annual Financial Report document or Annual Report published on the official website of each Islamic Commercial Bank. The number of samples is 7 Islamic Commercial Banks in Indonesia. Data will be processed using Microsoft Excel. The method used in this study is quantitative research with a descriptive approach. The results of the study have been conducted using the Sharia Conformity method with four quadrants, namely the Upper Right Quadrant (URQ), Lower Right Quadrant (LRQ), and Upper Left Quadrant (ULQ).